59.7k views
4 votes
If s(x)=x-7 and t(x)=4x^2-x+3 which expression is equivalent to (t•s)(x)?

4(x-7)^2-x-7+3
4(x-7)^2-(x-7)+3
(4x^2-x+3)-7
(4x^2-x+3)(x-7)

2 Answers

5 votes
hello :
s(x)=x-7 and t(x)=4x²-x+3
(t•s)(x) = t(s(x)) = t(x-7) = 4(x-7)²-(x-7) +3
(t•s)(x) = 4(x-7)²-x+7+3
User Rex Logan
by
6.4k points
3 votes

Answer: (B)
4(x-7)^2-(x-7)+3.

Step-by-step explanation: We are given the following two functions :


s(x)=x-7,\\\\t(x)=4x^2-x+3.

We are to find the expression that is equivalent to
(t.s)(x).

We know that

for any two functions f(x) and g(x), we have


(f.g)(x)=f(g(x)).

Therefore, we get


(t.s)(x)\\\\=t(s(x))\\\\=t(x-7)\\\\=4(x-7)^2-(x-7)+3.

Thus,
(t.s)(x) is equivalent to
4(x-7)^2-(x-7)+3.

Option (B) is CORRECT.

User Tutul
by
6.1k points